Light-induced mechanistic divergence in gold(I) catalysis: revisiting the reactivity of diazonium salts - Taschinski, Svenja; Döpp, René; Ackermann, Martin; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie, 2019)
In a systematic study of the Au-catalyzed reaction of o-alkynylphenols with aryldiazonium salts, we find that essentially the same reaction conditions lead to a change in mechanism when a light source is applied. If the reaction is carried out at room temperature using a AuI catalyst, the diazonium salt undergoes electrophilic deauration of a vinyl AuI intermediate and provides access to substituted azobenzofurans. If the reaction mixture is irradiated with blue LED light, C−C bond formation due to N2-extrusion from the diazonium salt is realized selectively, using the same starting materials without the need for an additional photo(redox) catalyst under aerobic conditions. We report a series of experiments demonstrating that the same vinyl AuI intermediate is capable of producing the observed products under photolytic and thermal conditions. The finding that a vinyl AuI complex can directly, without the need for an additional photo(redox) catalyst, result in C−C bond formation under photolytic conditions is contrary to the proposed mechanistic pathways suggested in the literature till date and highlights that the role of oxidation state changes in photoredox catalysis involving Au is thus far only poorly understood and may hold surprises for the future. Computational results indicate that photochemical activation can occur directly from a donor-acceptor complex formed between the vinyl AuI intermediate and the diazonium salt.
Gesehen am 04.12.2019